PREPARASI DAN KARAKTERISASI KOMPOSITSELULOSA BAKTERIAL-EKSTRAK DAUN KACA PIRING(Gardenia augusta) UNTUK APLIKASI BIOMEDIS - Silvia Dewi Sartika; Ananda Putra; Ali Amran (Jurnal Periodic Jurusan Kimia UNP, 2016)
Bacterial Cellulose (BC) was fermented coconut water with the aid of Bacteria Acetobacter xylinum. The generated BC became composite by adding a natural ingredient of Ectract of Gardenia augusta Leaves (EGAL). Gardenia augusta leaves was an annual shrub of the coffee genus or rubiaceae. Gardenia augusta leaves contain of chemicals such as flavonoids, saponins, tanins, galat and steroid or terpenoids. This research aimedat determining the effect of immersion time of Bacterial Cellulose in EGAL within 1,2,3 and 4 days onphysical properties (water content), mechanical properties (Compressive Strength using Toni technik Compressive Test Bauform Model 2020 and Tensile Strength using Buchel B.V Horizontal Tensile Tester model No. K465,item 84-58-00-0002 range 500N, 230V-50Hz), and Structural (Functional Groups using FTIR and Crystalinity using XRD) against Composite Bacterial Cellulose-Ectract of Gardenia augusta Leaves (CBC-EGAL) produced. The results showed the water content test,compressive strength test and the tensile strength test of CBC-EGAL are still belowed the minimum standard of articular cartilage. It was caused by least EDKP that goes into the matrix (SB).EGAL also could increase modulus young of BC. The result of XRD spectra and FTIR difractogram  showed that BC and CBC-EGAL wasbelonging to cellulose type-I.